Analysis Of The Influence Of Marketing Techniques And Ways Of Business Management On The Income Level Of Micro Small And Medium Enterprises (MSME’s) In Kediri City - Leonis, Angelina Rahmawati; Prasetyo, Eko; Paradita, Bella (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This study aims to analyze the influence of marketing techniques and business management methods on the income level of Micro, Small, and Medium Enterprises (MSMEs) in Kediri City, focusing on Tahu Village in Tinalan District. Design/Methode/Approach: Quantitative research methods were employed for this study, utilizing observation, interviews, and questionnaires for data collection. Statistical analyses, including hypothesis testing, coefficient of determination, t-test, and F-test, were conducted using SPSS 25. Research Finding: The research revealed that both marketing techniques and business management methods significantly influence the income levels of MSMEs in Tahu Village. Marketing techniques were found to have a coefficient value of 0.149, while business management methods had a coefficient value of 0.309. The F-test indicated a joint positive influence of these variables on income levels. Theoretical contribution/Originality: The study contributes to existing literature by demonstrating the significance of marketing techniques and business management methods in enhancing MSME income. It aligns with previous research emphasizing the importance of factors such as price, place, promotion, and product quality in marketing success. Practitioner/Policy implication: The findings underscore the importance of implementing effective marketing strategies and sound business management practices for MSMEs to thrive. Policy implications suggest the need for targeted assistance and training programs to enhance MSMEs' understanding and implementation of these techniques. Research limitation: This study was limited to Tahu Village in Tinalan District, Kediri City, thus its generalizability to other contexts may be constrained. Additionally, the sample size was small, potentially limiting the representativeness of the findings.